GOOD GOVERNANCE DALAM PROGRAM PEMBINAAN ATLET BERPRESTASI PADA AJANG POPDA RIAU OLEH DINAS KEPEMUDAAN DAN OLAHRAGA KOTA PEKANBARU TAHUN 2016 DAN 2018 - Sasela, Eni; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Good governance is the basis for the formulation and implementation of democratic state policies in the era of globalization with absolute requirements for the realization of good governance based on responsibility, transparency, and participation. Achievement sports are carried out with a planned coaching and development process, therefore the government is obliged to organize and supervise the process of growth and development of sports achievements in a province rooted in coaching at the district/city level. The writing of this thesis was motivated by the researcher's view of the phenomenon that occurred in the Riau Regional Student Sports Week (POPDA) competition which was followed by Pekanbaru to get the overall champion in a row but the sepak takraw branch failed for two consecutive years. The formulation of the problem in this study is how good governance is in the program for coaching outstanding athletes at the Riau POPDA event by the Pekanbaru City Youth and Sports Office in 2016-2018. This study aims to describe Good Governance in the coaching program for outstanding athletes at the Riau POPDA event by the Youth and Sports Office of Pekanbaru City 2016-2018.The research approach used is a qualitative approach. This type of research is descriptive. The research location is in Pekanbaru City. With the type and source of research data, it is divided into primary data in the form of purposive informant retrieval techniques and secondary data in the form of supporting data related to outstanding athletes. Data collection techniques used interviews and documentation, while data analysis was carried out using qualitative analysis.The results of this study indicate that the implementation of the principles of good governance, especially the principles of participation, effectiveness and accountability principles are running optimally but there are several obstacles such as the lack of facilities and infrastructure for the sport of sepak takraw and the lack of interest in the sport which must be borne by the government in order to improve athlete achievement..Keywords: Â Good Governance,Coaching, Sports, Athletes